PEMAHAMAN HADITS MENURUT YUSUF AL-QARADHAWI - Syaiful Nazaar (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Hadith is the sayings or actions of the Prophet that serve as the second source of law for Muslims. Unlike the Qur'an, there is no factual guarantee ensuring the truth of hadith texts, which has led to various scholarly perspectives among hadith scholars, one of whom is Yusuf Al-Qardhawi. The purpose of this research is to explore how Yusuf Al-Qardhawi interprets hadith. This study uses the Library Research method. The results of this research indicate that in understanding the hadith of Prophet Muhammad SAW, Al-Qardhawi emphasizes nine important principles, which include: it must align with the Qur'an, integrating hadiths with similar themes, prioritizing hadiths that are in conflict, analyzing the background, context, and orientation of the hadith, distinguishing between inconsistencies in the means and the consistency of the objectives of the hadith, comparing literal and figurative expressions in the interpretation of hadith, contrasting the unseen with the seen, and validating hadith terminology.